A case of tracheal stenosis due to anaplastic thyroid carcinoma treated using the stent‐in‐stent method - Tadashi Sakaguchi; Maki Ohi; Yoichi Nishii; Osamu Hataji (Thoracic Cancer, 2024)
Abstract Tracheal AERO stent collapse is a rare complication compared to bronchial AERO stent collapse due to differences in the nitinol framework thickness. A 58‐year‐old man with a bulky anaplastic thyroid carcinoma was referred to our hospital due to exacerbation of tracheal stenosis despite the administration of lenvatinib. His tracheal stenosis exhibited a severe extrinsic compression pattern with a length of 8 cm. Because tracheotomy was inappropriate, we placed an 18 × 80 mm AERO stent. Five months later, he was readmitted with severe dyspnea due to collapse of the distal portion of the stent caused by tumor growth. Because stent removal was difficult, we placed an additional AERO stent (18 × 60 mm) to cover the collapsed portion. The additional stent successfully expanded the collapse and improved his dyspnea. To our knowledge, this is the first case where a tracheal AERO stent collapse due to a poor prognosis tumor was treated with the stent‐in‐stent method.